Improving Students’ Mathematical Reasoning Ability through the Use of the Joyful Learning Model Assisted by GeoGebra - Silpa Rahmawati; Ipah Muzdalipah; Siska Ryane Muslim (Kognitif: Jurnal Riset HOTS Pendidikan Matematika, 2026)
The mathematics learning process in schools often faces challenges such as low student engagement, limited conceptual understanding, and the dominance of less interactive teaching approaches. These conditions hinder the development of higher-order thinking skills, particularly students’ mathematical reasoning ability. Therefore, innovative and technology-assisted learning models are required to improve the effectiveness of mathematics instruction. This study aims to examine the improvement of students’ mathematical reasoning ability through the implementation of the Joyful Learning model assisted by GeoGebra. The research employed an experimental method using a One Group Pretest–Posttest Design. The population consisted of all seventh-grade students of SMP 3 Al-Muhajirin, while the sample comprised 29 students from Class VII E selected using a simple random sampling technique. Data were collected using an essay-based test designed to measure mathematical reasoning ability and administered before and after the learning intervention. Statistical analysis was conducted using normality testing and the Wilcoxon signed-rank test with the support of IBM SPSS Statistics 24. The results indicate a statistically significant difference between pretest and posttest scores, showing an improvement in students’ mathematical reasoning ability after the implementation of the Joyful Learning model assisted by GeoGebra. This improvement reflects students’ enhanced ability to propose conjectures, identify patterns, apply mathematical manipulation, and draw logical conclusions. These findings suggest that the integration of the Joyful Learning model and GeoGebra is an effective instructional approach for fostering mathematical reasoning ability and creating a more engaging mathematics learning environment.